Analysis of the implementation of the national pharmaceutical assistance policy in the Brazilian Unified Health System (SUS): Achievements and challenges (Revista Contexto & Saúde, 2026)
Pharmaceutical Assistance plays a crucial role in achieving the goals of the 2030 Agenda for Sustainable Development, especially with regard to promoting health and well-being for all. Despite the achievements resulting from decades of implementation of the National Pharmaceutical Assistance Policy in Brazil, numerous challenges are still reported. Understanding these elements is fundamental to strengthening health systems, contributing to the construction of healthier and more resilient societies. Therefore, the objective of this study was to describe the achievements and challenges of the National Pharmaceutical Assistance Policy in the Unified Health System (SUS). A systematic literature review was conducted, including 17 studies. The results show that several actions have progressed positively, reflecting across all fields of Pharmaceutical Assistance. However, several aspects to be included, reorganized, and improved were also identified, especially in relation to Public Policies and Management, highlighting deficiencies in service management as one of the main challenges. In conclusion, the results demonstrate the diversity of conceptions found in Pharmaceutical Assistance, reflecting the ongoing movement in the process of reorienting its implementation. The critical and integrated analysis of these results contributes to addressing the prevalent challenges in primary health care, including access to medicines and pharmaceutical care in Brazil. This research provides relevant evidence to improve the policy and management of Pharmaceutical Assistance, aiming to enhance the quality of services provided and, consequently, the health of the population benefited by the Unified Health System.
Keywords: Pharmaceutical Assistance; Unified Health System; Public Policies